Self‐Calibrated, Sensitive, and Flexible Temperature Sensor Based on 3D Chemically Modified Graphene Hydrogel. (27th January 2021) - Wu, Jin; Huang, Wenxi; Liang, Yuning; Wu, Zixuan; Zhong, Bizhang; Zhou, Zijing; Ye, Jindong; Tao, Kai; Zhou, Yubin; Xie, Xi
Abstract: During the long‐term operation of temperature sensors, periodical calibration is required to achieve accurate readings, which usually requires bulky and costly heating facilities for calibration. Herein, a new kind of self‐calibrated thermistors using embedded microheaters as a self‐heating platform are proposed for in situ, convenient, cost‐effective, and fast self‐calibration. Furthermore, the thermal sensing properties of 3D reduced graphene oxide hydrogel (RGOH) is explored for the first time based on this microheater platform. It is found that the a 3D sulfonated RGOH (S‐RGOH) based thermistor displays high sensitivity (2.04% K −1 ), extraordinary resolution (0.2 °C), a broad detection range (26–101 °C), good repeatability, and stability. The thermal sensitivity of S‐RGOH is far superior to that of pristine RGOH, revealing the remarkable role of chemical modification in enhancing temperature sensing performance. In addition to self‐calibration, the microheaters are also used for characterizing temperature‐dependent properties and thermal annealing of S‐RGOH in situ. The thermal sensing mechanism is proposed and the high sensitivity is discussed by considering the abundant functional groups, defects, and 3D porous structure of S‐RGOH. The flexible S‐RGOH thermistor fabricated on a liquid crystal polymer substrate is immune to mechanical flexion, allowing for various practical applications in future wearable electronics. Abstract : Self‐calibrated thermistors are fabricated using integrated microheaters as a self‐heating platform for calibration, characterization of thermal‐sensitive materials, and thermal annealing simultaneously, without entailing external heating facilities. 3D chemically modified (sulfonated) reduced graphene oxide hydrogels are exploited as channel materials of flexible thermistors to achieve high sensitivity (2.04% K −1 ), extraordinary resolution (0.2 °C), and a broad detection range (26 – 101 °C).